1993
DOI: 10.1111/j.1432-1033.1993.tb18270.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 100‐kDa protein associated with nuclear ribonuclease P activity in Schizosaccharomyces pombe

Abstract: Ribonuclease P from the fission yeast Schizosaccharomyces pombe has been purified to apparent homogeneity. A purification of 23 000-fold was achieved by four fractionation steps with DEAEcellulose chromatography, phosphocellulose chromatography, glycerol-gradient fractionation and finally tRNA-affinity chromatography. A 100-kDa protein was present in the most pure preparations in amounts approximately stoichiometric with the previously identified RNA components of the enzyme, K1-RNA and K2-RNA {Krupp, G., Cher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The fact that wheat germ RNase P is not inactivated by micrococcal nuclease suggests that its overall structure might be similar to that of other eukaryotic and also archaebacterial enzymes, with a relatively large protein subunit protecting the RNA from nuclease attack and contributing to the low density of the holoenzyme. Indeed, eukaryotic and archaebacterial RNases P tend to possess much larger protein subunits than the bacterial enzymes, as estimated from the size of the holoenzymes (Kmpp et al, 1986;Lee and Engelke, 1989;Bartkiewicz et al, 1989;Morales et al, 1989;Darr et al, 1990) and also after direct identification of the protein component (Morales et al, 1992;Dang and Martin, 1993;Zimmerly et a]., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that wheat germ RNase P is not inactivated by micrococcal nuclease suggests that its overall structure might be similar to that of other eukaryotic and also archaebacterial enzymes, with a relatively large protein subunit protecting the RNA from nuclease attack and contributing to the low density of the holoenzyme. Indeed, eukaryotic and archaebacterial RNases P tend to possess much larger protein subunits than the bacterial enzymes, as estimated from the size of the holoenzymes (Kmpp et al, 1986;Lee and Engelke, 1989;Bartkiewicz et al, 1989;Morales et al, 1989;Darr et al, 1990) and also after direct identification of the protein component (Morales et al, 1992;Dang and Martin, 1993;Zimmerly et a]., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A temperature-sensitive mutant of rprl accumulates pre-tRNAs that are spliced but 5' and 3' unprocessed (Lee et al 1991). Analysis of the protein components of the nuclear RNase P from S. cerevisiae has not been reported; however, highly purified RNase P from Schizosaccharomyces pombe contains a single protein component of 100 kD estimated molecular mass (Zimmerly et al 1993). RNase P from vertebrates can be immunoprecipitated by human Th autoim-Cold Spring Harbor Laboratory Press on May 12, 2018 -Published by genesdev.cshlp.org Downloaded from mune sera (also called To sera) .…”
mentioning
confidence: 99%
“…polypeptide because other known eukaryotic nuclear RNase P are made up of a single large polypeptide (Zimmerly et al, 1993). The following evidence confirmed that nuclear RNase P Characterization of the RNA component of nuclear RNase P. To determine whether the RNA component is an essential was composed of a seven-polypeptide complex.…”
Section: Discussionmentioning
confidence: 76%
“…This means that eukaryotic RNase P is more proteinaceous lus species) is about 150 kDa (Darr et al, 1992) and the buoyant than its bacterial counterpart. Second, the molecular mass of density of RNase P of E. coli (Lawrence et al, 1987) and Haloeukaryotic RNase P is greater than that of its bacterial counterferax volcanii (Nieuwlandt et al, 1987) in a cesium sulfate grapart [for example, the molecular mass of RNase P of Saccharodient are 1.55 g/cm 3 and 1.61 g/cm 3 , respectively. The length of myces pombe is about 450 kDa (Kline et al, 1981; Krupp et al, the RNA component of bacterial RNase P is 340Ϫ400 nucleo-1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation